Co-Deposition and Poisoning of Chromium and Sulfur Contaminants on La0.6Sr0.4Co0.2Fe0.8O3-δ Cathodes of Solid Oxide Fuel Cells. Issue 6 (24th February 2015) - Wang, Cheng Cheng; O'Donnell, Kane; Jian, Li; Jiang, San Ping
Abstract : The presence of both chromium and sulfur (Cr/S) contaminants on the microstructure and electrocatalytic activity properties of La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) electrodes of solid oxide fuel cells (SOFCs) is studied, using Confocal laser Raman spectroscopy, XRD, scanning electron microscopy, X-ray photoelectron spectroscopy (XPS) and electrical conductivity relaxation (ECR) methods. LSCF dense bar samples were heat treated in the presence of Cr2 O3 and 20 ppm SO2 and in the temperature range of 600–900°C. The deposition and reaction products between LSCF and Cr/S depend on the temperature: SrCrO4 only forms on LSCF samples at 900°C and 800°C, while formation of SrSO4 phase occurs at all temperatures studied. The results indicate that sulfur shows a higher activity with LSCF, as compared to gaseous Cr species. Segregated SrO is more likely to react with gaseous Cr species at higher temperatures, however, reaction with SO2 is more pronounced at lower temperatures, forming SrSO4 . ECR results indicate that co-deposition of Cr and sulfur significantly deteriorates the surface exchange and diffusion processes for the O2 reduction reaction on LSCF electrodes.